Understanding Self-gift Consumer Behaviour (SGCB)in China: How culture influences SGCB. - Sun, Luping (2007)
This dissertations aims to understand self-gift consumer behaviour (SGCB) in China, specifically its nature and role, the contexts triggering it, and the emotions that it involve. The cultural influence on the experience of SGCB between Chinese and Western consumers is also aimed to achieve. Considering the first attempt to study SGCB in the Chinese context, and the subjective nature of the research, exploratory in-depth interviews were employed. By using snowball sampling technique, twelve Chinese consumers were chosen to take part in the interviews. This study not only supports and confirms existing literature in certain aspects of SGCB, but discovers the unique features of SGCB experience in the context of China. The motivations and emotions associated with Chinese SGCB are found far more complex than those in the Western countries. More psychological investments are made by Chinese consumers, whose culture is not in accordance with the self-centred consumer behaviour.